A Non-infringing Route for Enantioselective Synthesis of Antiepileptic Agent Lacosamide - Wadavrao, Sachin B.; Narikimalli, Ashritha; Narsaiah, A. Venkat (Synthesis, 2013)
A non-infringing route for enantioselective synthesis of lacosamide has been developed. The synthesis started from commercially available acrylic acid and was completed in eight steps using Sharpless asymmetric dihydroxylation as a key step with an overall yield of 29%. All the reactions were very clean with good yields.
Keywords: antiepileptic agent; dihydroxylation; tosylation; azide; lacosamide